Drugs in early clinical development for Systemic Lupus Erythematosus. (3rd May 2016) - Postal, Mariana; Sinicato, Nailú Angélica; Appenzeller, Simone; Niewold, Timothy B.
ABSTRACT: Introduction : While immunosuppressive therapy has positively impacted the prognosis of systemic lupus erythematosus (SLE), many patients still do not respond to traditional therapy. Thus, active SLE disease remains a significant problem. Furthermore, conventional immunosuppressive treatments for SLE are associated a high risk of side effects. These issues call for improvement in our current therapeutic armamentarium. Areas covered : In this review, the authors highlight the recent developments in therapies for SLE, and present an overview of drugs which are in early clinical development for SLE. There are many new therapeutic approaches being developed, including those focused on B-cell targets, T-cell downregulation, co-stimulatory blockade, anti-cytokine agents, and kinase inhibition, and Toll-like receptor inhibition. They also discuss peptide therapy as a potential method to re-establish immune tolerance, and some of the challenges ahead in developing and testing novel agents for SLE. Expert opinion : Many novel agents are currently in development for SLE, but this encouraging news is tempered by several disappointments in clinical trials and provides a timely moment to reflect on the future of therapeutic development in SLE. It seems likely that biological heterogeneity between patients is a major contributor to difficulty in drug design in SLE.